1998
DOI: 10.1007/s001270050092
|View full text |Cite
|
Sign up to set email alerts
|

Suicide following an inpatient hospitalization for a suicide attempt: a Canadian follow-up study

Abstract: This study contributes a Canadian perspective to a growing body of international studies examining suicide among cohorts of suicide attempters, and a much more limited literature on the epidemiology of suicide in Canada. We evaluated the 13-year mortality experience of a regional cohort of 876 first-ever inpatient hospital admissions for a suicide attempt admitted between 1979 and 1981. Compared to the general population, study subjects were 4 times more likely to die of any cause, but 25 times more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 0 publications
6
33
1
1
Order By: Relevance
“…Similar results were found more recently in follow-up studies conducted in Austria, Australia and Finland among patients who had attended hospital because of self-poisoning or attempted suicide; in each case there were clear excesses of deaths due to natural and unnatural causes [1,2,22]. On the other hand, a Canadian study found that patients admitted to inpatient psychiatric care following a suicide attempt were significantly less likely than the population in general to die of natural causes [17].…”
Section: Introductionsupporting
confidence: 66%
“…Similar results were found more recently in follow-up studies conducted in Austria, Australia and Finland among patients who had attended hospital because of self-poisoning or attempted suicide; in each case there were clear excesses of deaths due to natural and unnatural causes [1,2,22]. On the other hand, a Canadian study found that patients admitted to inpatient psychiatric care following a suicide attempt were significantly less likely than the population in general to die of natural causes [17].…”
Section: Introductionsupporting
confidence: 66%
“…8,14 The results of the current study indicate that NFSB is more common in the younger age group. Pillay et al 22 and Schlebusch 23 in South Africa obtained similar results.…”
Section: Discussionmentioning
confidence: 62%
“…7,8,9 Another strong risk factor for NFSB is a history of psychiatric disorder. 10,11,12,13 Increasing age 8,14 , living alone 15 or in a low-income area 8 , mental illness 14 , somatic illness 7,16 and the abuse of alcohol and drugs 15 have also been identified as risk factors. Some medical illnesses, such as spinal cord injuries and multiple sclerosis 17 , are associated with increased rates of NFSB, but the evidence of this association is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide risk has appeared to be highest during the first two or three years after an index suicide attempt for patients with mixed diagnoses according to several investigators (Hawton & Fagg 1988, Nielsen, Wang & Bille-Brahe 1990, Ekeberg, Ellingsen & Jacobsen 1991, Nordentoft et al 1993, Johnsson-Fridell, Öjehagen A & Träskman-Bendz 1996, Tejedor 1999, Suokas et al 2001 or for patients with unipolar depression and bipolar disorder (Tidemalm et al 2008). A highest peak after a first-ever hospitalization for a suicide attempt was found in the fourth year (Holley, Fick & Love 1998).…”
Section: Introductionmentioning
confidence: 99%